Care pathway and prioritization of rapid testing for COVID-19 in UK hospitals: a qualitative evaluation - Timothy Hicks; Amanda Winter; Kile Green; Patrick Kierkegaard; D. Ashley Price; Richard Body; A. Joy Allen; Sara Graziadio; CONDOR Steering Group (BMC, 2021)
Abstract Objectives The second wave of the coronavirus pandemic is now established, occurring at a time of winter pressure on acute care in the NHS. This is likely to be more challenging then the first wave for the diagnosis of COVID-19 because of the similar symptomology with other respiratory conditions highly prevalent in winter. This study sought to understand the care pathways in place in UK NHS hospitals during the first wave (March-July 2020) for identification of patients with COVID-19 and to learn lessons to inform optimal testing strategies within the COVID-19 National Diagnostic Research and Evaluation Platform (CONDOR). Design, setting & participants Sixteen hospital-based clinicians from 12 UK NHS Trusts covering 10 different specialties were interviewed following a semi-structured topic guide. Data were coded soon after the interviews and analysed thematically. Results We developed a diagrammatic, high-level visualisation of the care pathway describing the main clinical decisions associated with the diagnosis and management of patients with suspected COVID-19. COVID-19 testing influenced infection control considerations more so than treatment decisions. Two main features of service provision influenced the patient management significantly: access to rapid laboratory testing and the number of single occupancy rooms. If time to return of result was greater than 24 h, patients with a presumptive diagnosis would often be cohorted based on clinical suspicion alone. Undetected COVID-19 during this time could therefore lead to an increased risk of viral transmission. Conclusions During the winter months, priority for provision of rapid testing at admission should be given to hospitals with limited access to laboratory services and single room availability. Access to rapid testing is essential for urgent decisions related to emergency surgery, maternity services and organ transplant. The pathway and prioritization of need will inform the economic modelling, clinical evaluations, and implementation of new clinical tests in UK.